Latissimus dorsi transfer: L'Episcopo versus Herzberg technique - Moursy, Mohamed; Cafaltzis, Konstantinos; Eisermann, Simone; Lehmann, Lars (Acta orthopaedica belgica, 2012)
The purpose of this study was to compare the clinical results of two different techniques of latissimus dorsi transfer used in 28 patients, either a modified single incision mini-invasive Herzberg transfer (HT) or a combined latissimus dorsi and teres major transfer according to L'Episcopo (LE). Twenty-eight patients fulfilled the inclusion criteria. Minimum follow-up was 24 months. Sixteen patients were treated with the Herzberg transfer (HT group) and 12 patients had the L'Episcopo technique (LE group). The Constant score rose from 272 initially to 73.5 four years post-operatively in the LE group and from 32.2 to 76 three years and 3 months post-operatively in the HE group (statistically similar). The pre-operative acromiohumeral distance remained unchanged statistically. Radiological signs of osteoarthritis increased. Constant-Murley score, acromiohumeral distance and progression of rotator cuff tear arthropathy were not significantly different between the two groups.